An investigation into virtual objects learning by using haptic interface for visually impaired children - Chit, Su Mon *; Yap, Kian Meng * (2011)
It is well known that visually impaired children have limited opportunities in learning new things compared to normal sighted children as visually impaired children do not have one of the important senses of human being. Computer simulated virtual reality environment can provide better opportunities for visually impaired children especially in learning the shapes of new objects. An application utilizes the force feedback technology i.e. haptic, together with an aid of audio has been developed in this research project. This allows visually impaired users to have a better learning environment. It assists visually impaired children in learning the shapes of different objects and also memorizing the shapes of different objects. In addition, the program will help users to train their memory by memorizing the names of different objects together with the shapes. This creates a new application in a novel research area which will help the visually impaired children in their learning process.